2009
DOI: 10.1007/s10456-009-9143-7
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress-induced transcriptional regulation via hybrid promoters as a potential tool for promoting angiogenesis

Abstract: Among the key effects of fluid shear stress on vascular endothelial cells is modulation of gene expression. Promoter sequences termed shear stress response elements (SSREs) mediate the responsiveness of endothelial genes to shear stress. While previous studies showed that shear stress responsiveness is mediated by a single SSRE, these endogenous promoters often encode for multiple SSREs. Moreover, hybrid promoters encoding a single SSRE rarely respond to shear stress at the same magnitude as the endogenous pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 61 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…The presence of promoter sequences termed shear stress response elements (SSREs) has been proposed to mediate the responsiveness of EC genes to shear stress. Although a single SSRE (the sequence GAGACC) was reported to encode shear stress responsiveness in endothelium (121,131), promoter regions of genes may encode for multiple SSREs (100,127). On the other hand, more recent studies have shown that transcriptional changes seen with flow also may be independent of SSREs (136).…”
Section: Onset Of Flow and Flow Adaptationmentioning
confidence: 99%
“…The presence of promoter sequences termed shear stress response elements (SSREs) has been proposed to mediate the responsiveness of EC genes to shear stress. Although a single SSRE (the sequence GAGACC) was reported to encode shear stress responsiveness in endothelium (121,131), promoter regions of genes may encode for multiple SSREs (100,127). On the other hand, more recent studies have shown that transcriptional changes seen with flow also may be independent of SSREs (136).…”
Section: Onset Of Flow and Flow Adaptationmentioning
confidence: 99%
“…Promoters comprising AP1 response elements have been shown to respond to mechanical strain, as were elements comprising binding sites for SP1 or NFkB . A consensus shear stress responsive element SSRE (GAGACC) has been described to be activated especially in systems related to the vasculature (Inoue et al, 2004;Kletsas et al, 2002;Liedert et al, 2006b;Liedert et al, 2009;Miyagi et al, 2005;Ogasawara et al, 2001;Peverali et al, 2001;Silberman et al, 2009;Sumpio et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Moving forward, one possible approach to enhance the sensor sensitivity would be through optimizing inducible promoter region. It is important to note that shear stress pathways are complicated and the complex interplay of between shear stress response elements in shear sensitive gene promoters has not been fully elucidated 52 . However we anticipate that careful construction of the promoter using a concoction of shear inducible elements could develop the sensitivity for finer resolution sensing of shear induced pathway activation.…”
Section: Discussionmentioning
confidence: 99%